Successful management of a recurrent hepatosplenic metastatic nasopharyngeal carcinoma in an adolescent boy: case report and review of literature - Ramesh, Varsha; Sneha, Latha M.; Muralitharan, Sushruthan; Jayaraman, Dhaarani (International Journal of Contemporary Pediatrics, 2021)
Nasopharyngeal carcinoma (NPC) is a rare tumor in pediatric age group and adolescents are the commonly affected age group. It generally presents as locoregionally advanced disease and 15-30% of them develop a recurrence or distant metastatic disease. The outcome of patients with recurrent metastatic nasopharyngeal carcinoma has been reported to be very poor, with a median overall survival of about 20 months. We present a case of adolescent boy who presented initially with locally advanced nasopharyngeal carcinoma, treated with local radiotherapy and cisplatin, 5 flurouracil and later presented with a recurrent metastatic disease in liver and spleen, within 2 months of completing treatment. He was managed with total splenectomy and paclitaxel and gemcitabine and he remains disease free for more than 18 months now. The case highlights that long term remission could be attained with conventional chemotherapy, combined with surgery in relapsed metastatic NPC even in a resource limited settings.